Refleksi Pandemi Covid-19 dalam Akselerasi Tujuan Pembangunan Berkelanjutan - Handoko, Chanel Tri; Fitria, Syarifa (ENVIRO: Journal of Tropical Environmental Research, 2022)
The world's response to the Covid-19 pandemic would impact the target of achieving the 17 Sustainable Development Goals SDGs) in 2030. When the world needed to accelerate the achievement of SDGs targets, the Covid-19 pandemic brought global uncertainty. This study discussed several lessons from the Covid-19 pandemic and the impact of the pandemic in accelerating the achievement of the 17 SDGs targets. This research was conducted using a qualitative approach with bibliometric and descriptive evaluative analysis methods. The study results revealed that although it caused a global economic contraction and various health problems, the Covid-19 pandemic should be used as a momentum to evaluate and make necessary improvements in achieving the SDGs in 2030. Based on this study, all SDGs goals have an integrated nature, so that progress towards one SDG goal would affect the other goals. Therefore, global collaborative efforts from all stakeholders are needed to achieve the 17 SDGs targets.